Analisis Keterkaitan Komponen Kurikulum sebagai Sistem dalam Kurikulum Merdeka di Sekolah Dasar - Anazah; Sofyan Iskandar; Kinanti Dilla Putri; Yosha Sheptia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The curriculum plays a crucial role in shaping the direction and quality of education. The Merdeka Curriculum was developed in response to post-pandemic educational challenges, emphasizing flexibility, project-based learning, and character development. This study aims to analyze the interrelation between components of the Merdeka Curriculum as an integrated system and to evaluate its strengths and weaknesses in implementation. The method used is a literature review, involving the examination of various scholarly sources to gain a comprehensive understanding. The analysis reveals that the Merdeka Curriculum consists of four main components goals, content, process, and evaluation which are closely interconnected. Teachers play a vital role in aligning these components to ensure effective learning. The curriculum offers advantages such as essentialized content, greater instructional autonomy, and student-centered assessment. However, challenges include limited teacher training, uneven infrastructure, and varying interpretations in practice. Therefore, optimizing the Merdeka Curriculum requires enhancing teacher competencies and systemic support to fully achieve educational objectives in a holistic manner.